Genetics of Lactose Intolerance: Minireview - Mahdi, Zena Abdul-Ameer; Al-Khafaji, Noor S. K.; Al-Dahmoshi, Hussein O.M.; Akram, Muhammad; Rashid, Abid; Waqas, Syed Muhammad; Riaz, Tehreem; Laila, Umme; Zainab, Rida; Zainab, Rida; Iftikhar, Momina; Khalil, Muhammad Talha; et al. (Jour Med Resh and Health Sci, 2023)
The capacity for lactose digestion, which is the predominant source of carbohydrates and nutrition present in milk, is inherited in the majority of people. Lactase is encoded by a gene, LCT and there are two possible polymorphisms of this gene were sequenced. The first is C/T, where the second polymorphism is G/A .Around 75 percent population of the world lose their lactose digesting ability ,It occurs when the activity of lactase in the intestine is reduced or absent, at some time in their lives, whereas some can digest lactose until they reach maturity. Increased risk of developing various pathologies for lactose-intolerant subjects (some types of cancer, osteoporosis) indicate how important to diagnose and properly treat this pathology. The deficit capacity to digest lactose, its diagnosis and the sign and symptoms and therapy are all going to be discussed in this paper.